The pivotal role of the NLRC4 inflammasome in neuroinflammation after intracerebral hemorrhage in rats - Hui Gan (Nature Publishing Group, 2021)
Brain hemorrhage: Reducing inflammation and brain damage Treatments that target the proteins responsible for inflammation might reduce brain damage after a hemorrhage. Sudden bleeding into the brain, known as intracerebral hemorrhage (ICH), is associated with strokes and head injuries. Inflammation exacerbates ICH-induced injury after an incident, and is activated by protein complexes called inflammasomes. Jing Zhao and co-workers at Chongqing Medical University in China induced ICH symptoms in rats by extracting arterial blood and injecting it into the basal ganglia of the brain. When they artificially blocked expression of the inflammasome NLRC4, they saw reductions in neuron death, brain edema and damage to the blood-brain barrier. The team also identified a protein critical for activating NLRC4 and another protein that suppresses NLRC4. These findings could aid the development of treatments to block NLRC4 in the days after an ICH.